If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 = 5x + -20 Reorder the terms: -2 + 3x = 5x + -20 Reorder the terms: -2 + 3x = -20 + 5x Solving -2 + 3x = -20 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -2 + 3x + -5x = -20 + 5x + -5x Combine like terms: 3x + -5x = -2x -2 + -2x = -20 + 5x + -5x Combine like terms: 5x + -5x = 0 -2 + -2x = -20 + 0 -2 + -2x = -20 Add '2' to each side of the equation. -2 + 2 + -2x = -20 + 2 Combine like terms: -2 + 2 = 0 0 + -2x = -20 + 2 -2x = -20 + 2 Combine like terms: -20 + 2 = -18 -2x = -18 Divide each side by '-2'. x = 9 Simplifying x = 9
| 4x+3=43 | | -5=-6w | | 3z=2.6+1.3 | | x*x+x+4=0 | | 13y+2=20y-5 | | 19-(2x-3)=2(x+3)+3 | | 2y-10=4y | | 1.33*-20=x | | 4y-3x=8 | | 9t+7=90 | | 6(x+2)+7= | | 7-10x=82-31x | | 3x+13=2x-12 | | -3xy^3+7xy^3+(-xy^3)+(-3xy^3)= | | n^2-9n-18=0 | | 0.25(w-4)-0.75w=3 | | 6x^3+9x^2-2x=0 | | 25x^4y+40xy^3= | | 8-(x+9)=24 | | 8(3-2x)= | | 5x+4x+1= | | 4-5x=28+x | | 3x^2-32x+52=0 | | 2+y=2 | | 3y^2=-24y | | x+8y=67 | | -15-8x=9x+19 | | 3X+1=-9 | | (2x-3)=7 | | 2y-45=-y | | 2(a-1)-5a=7 | | x-2y=-13 |